Our labor of love: Socially just leadership education as civic leadership development. Issue 195 (5th May 2022) - Collins, Jasmine D.; Manning‐Ouellette, Amber; Neal, Brandi; Daglaris, Megan
Abstract: The chapter authors argue there is a distinct relationship between socially just leadership education and civic engagement, which transforms inequitable work to interrupt and reconstruct unjust systems and organizations through curricular learning and engagement. To cultivate advocacy, activism, and engaged citizenry, higher education administrators, faculty, and staff have a responsibility to engage practices for socially just leadership learning and development of college students through curricular and co‐curricular experiences.